PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN OUTDOOR LEARNING DI SEKOLAH DASAR - Riska Amaliya (Jurnal Pendidikan Sang Surya, 2024)
The aim to be achieved in this research is to improve social studies learning outcomes through the Outdoor Learning learning model for class V students at UPTD SDN 171 Barru through the application of the Outdoor Learning model. This type of research is class action research (Class Action Research) which consists of two cycles carried out in four meetings. Research procedures include planning, implementing actions, observing and reflecting. The subjects in this research were 6 class V students of UPTD SDN 171 Barru, consisting of 2 boys and 3 girls. The research results showed that in cycle I, out of 5 students, only 3 students or (40%) students achieved learning completeness that met the Minimum Completeness Criteria (KKM). The minimum completeness criteria (KKM) applied at this school is 70. Classically it has not been met because the average score obtained was 68 in the medium category. Meanwhile, in cycle II, out of 5 students, 5 students or (100%) students achieved learning completeness that met the Minimum Completeness Criteria (KKM). The minimum completeness criteria (KKM) applied at this school is 70 and classically it has been met, namely the average score obtained is 85 or is in the very high category. Based on the results of the research above, it can be concluded that the social studies learning outcomes of class V students at UPTD SDN 171 Barru through the application of the Outdoor Learning learning model have increased.